Eficácia de níveis de um blend de aditivos sobre o desempenho e a saúde intestinal de frangos de corte desafiados experimentalmente - Imperatori , Fabrício (2022)
The maintenance of good intestinal integrity and health are of fundamental importance so that production animals can be able to express their genetic potential. In order to measure the impact of different variables involved in the context of broiler production, it is necessary to apply experimental protocols that are capable of simulating the reality of the field, allowing the accurate evaluation of food additives. In this sense, we aim to evaluate the performance, morphology, and regenerative capacity of the intestinal mucosa, as well as to study intestinal microbiota responses and the immune response of birds fed with a blend of additives composed of zinc proteinate, hydrolyzed yeast and encapsulated sodium butyrate associated or not with the use of antibiotic growth promoter in broilers submitted or not to an enteric challenge proposal. This study was carried out in the experimental aviary of the Federal University of Paraná – Palotina campus. A total of 3,936 male broiler chicks (Ross AP95®) were used and the birds were housed on shavings bedding, with water and feed ad libitum and divided into a 6 x 2 factorial scheme (Negative control (NC), Positive control (PC); PC + 1.0kg of Blend of additives/ton of feed; NC + 0.5kg; NC + 1.0kg; NC + 1.5kg of Blend of additives/ton of feed Vs with and without experimental enteric challenge), with 8 replications per treatment and 41 birds each. At 14 days of age, birds in the challenged groups were inoculated into the coccidiosis vaccine pool containing 20 times the dose recommended by the manufacturer. Two days later (16th day), the challenged birds received an inoculum containing Escherichia coli (ATCC® 8739™) with a calculated concentration of 109 CFU/bird applied directly to the flock. The evaluation of body weight, average feed intake, weight gain, and feed conversion were performed weekly. The degree of warpage was evaluated at 28, 35 and 42 days of age. Fragments of intestinal segments were collected at 19 days of age after euthanasia procedure of two birds/repeat for evaluation of intestinal morphometry and analysis of the proliferative capacity of intestinal cells. Intestinal mucosal permeability was measured by assessing serum levels of fluorescein isothiocyanate (FITC-d). Cecal excreta samples were collected at 42 days of age from 7 birds per treatment to determine the short chain fatty acid (SCFA) profile. For the calculation of carcass yield, cuts and abdominal fat deposition, at 42 days, 60 birds were slaughtered per treatment. Statistical procedures were performed using analysis of variance (ANOVA) using the General Lineal Model (GLM) using the SAS statistical program and, when significant, the treatment means were compared using Tukey's test (p<0.05). The results of this evaluation indicate that the enteritis induction protocol proposed in this study was effective, with compromised performance (p<0.05) in relation to the group of birds that were not experimentally exposed to the challenge. The birds that did not receive AGP in the diets and were supplemented with 0.5kg and 1.5kg of inclusion of the blend of feed additives showed similar results for WG to those birds that received diets with AGP. When considering the post-challenge period and the total rearing period, the birds supplemented with 1.5kg of the feed additive blend were those that obtained the best (p<0.05) feed conversion rate, as well as the birds supplemented with 1.0kg of the blend associated with AGP showed higher (p<0.05) weight gain in relation to the other diets. The blend of food additives composed of zinc proteinate, hydrolyzed yeast and encapsulated sodium butyrate used in the diets of broilers from 1 to 42 days of age submitted or not to the enteric challenge proposed in this experiment provided results similar or even superior to those when using AGP. Thus, this Blend can be indicated to act as an alternative or together with AGP in the creation of broilers.